Soil solarization for controlling soil-borne pathogens in vegetable crops - RAJ, HARENDER; BHARDWAJ, M L (The Indian Journal of Agricultural Sciences, 2013)
Â A study was conducted during 1995-98 at Jachh to find out the effect of transparent polyethylene mulch on soil temperature, incidence of soilborne diseases, plant growth and yield of vegetable crops, Solar heating with transparent polyethylene mulch of a infected field in slimmer for 40 days under irrigated conditions reduced the incidence of soilborne diseases. Mulching with transparent polyethylene resulted in 14Â°C higher temperature at 8 em soil depth with an average maximum temperature of 50Â° C which was found lethal to soilborne pathogens. Incidence of different soil-borne diseases in solarized plots ranged between 0 and 6 % in different crops in comparison to 10-21 % in unsolarized plots.